A modernize tax administration model for revenue generation - Pantamee, Abdurrahman Adamu; Mansor, Muzainah (EconJournals, 2016)
Capacity of a government to finance it expenditure depend on the ability of tax system to generate adequate revenue, and the ability of tax system to generate significant revenue depend on the tax administration efficiency and effectiveness, however in most of the developing economies, tax administration is characterized by inefficiency and ineffectiveness.The objective of this paper is to develop a model, which will guide developing countries to reform their tax administration toward tax revenue generation.To achieve this, several previous tax administration models as well as theories of governance and performance were reviewed and analyzed.Moreover, the modernize tax administration model developed in this study consists of four components namely inputs, transformation process, output, and outcome, the paper concludes that significant reform means working through the entire modernize tax administration model.The limitation of the paper is that the model is not been tested.